The common difference is d = -4, since
-32 - (-28) = -4
-36 - (-32) = -4
-40 - (-36) = -4
and so on.
In the arithmetic sequence starting with
and common difference -4, the next term is obtained by adding -4 to the previous one:
![a_1 =-28](https://img.qammunity.org/2023/formulas/mathematics/college/85p6iz0l0h5ldzpd5yx3yc7p3aowczfc8v.png)
![a_2 = a_1 + d = -28 - 4 = -32](https://img.qammunity.org/2023/formulas/mathematics/college/tf2urk916105boasmo356s9c698lbdcs86.png)
![a_3 = a_2 + d = a_1+2d = -28-4*2 = -36](https://img.qammunity.org/2023/formulas/mathematics/college/2ol04scqxjw0dh95law737ulepzsvg0pbg.png)
![a_4 = a_3 + d = a_1+3d = -28-4*3 = -40](https://img.qammunity.org/2023/formulas/mathematics/college/guezcnms96oq5opvirww8has05k9vottcg.png)
and so on, up the n-th term
![a_n = a_(n-1)+d = a_1+(n-1)d = \boxed{-28-4(n-1)}](https://img.qammunity.org/2023/formulas/mathematics/college/r5tdfkq1255uvkch7zm75aojueazyydaz7.png)